Analisis Hukum Islam dan UU No. 8 Tahun 1999 terhadap Pengalihan Uang Kembalian Pada Barang: (Studi Kasus Toko SRC Enco Desa Cilaja Kecamatan Kramatmulya Kabupaten Kuningan) - Saleh, Mulyana; Alfauzi, Fikri (AL-MASHALIH (Journal of Islamic Law), 2025)
Over time, the buying and selling system that continues to develop can sometimes raise problems that are detrimental to consumers and violate legal corridors. One of them is the practice of diverting consumer’s change into goods. The phenomenon of diverting consumer’s change also occurred at the SRC Enco Store, Cilaja Village, Kramatmulya Sub District, Kuningan Regency. SRC Enco Store is one of today's grocery stores that provides a variety of daily needs for the community. In practice, the seller at the SRC Enco Store transfers the consumer's change into an item. This study aims to find out how the practice of transferring change into goods at the SRC Enco Store, Cilaja Village, Kramatmulya Sub District, Kuningan Regency. In addition, this study also aims to analyze how the practice of transferring change into goods at the SRC Enco Store, Cilaja Village, Kramatmulya Sub District, Kuningan Regency, is viewed from Islamic law and Law No. 8 of 1999. The research method used is a qualitative method. This research includes the type of field research. Data collection techniques used are interviews, observation and documentation. The results of this study are first, the practice of transferring change into an item that occurs at the SRC Enco Store in Cilaja Village, Kramatmulya Sub District, Kuningan Regency is carried out by asking for prior approval from the consumer, and explaining the reasons for transferring change into the item. The practice of transferring change for goods is also carried out on the basis of the principle of consensual or there is the mutual approval of the shop or the buyer. Second, the transfer of change into an item that occurred at the SRC Enco Store in Cilaja Village, Kramatmulya Sub District, Kuningan Regency is in accordance with Islamic Law, because both parties are pleased with each other and neither party feels wronged or harmed by the transfer, and does not conflict and does not cause disputes, and the rights of sellers and buyers are fulfilled. Third, the transfer of change into goods at the SRC Enco Store in Cilaja Village, Kramatmulya Sub District, Kuningan Regency has been in accordance with Law No. 8 of 1999 because the shop does not violate consumer rights and there is no element of violation in the transaction.